An Update of Twin Research in Spain: The Murcia Twin Registry. (10th December 2019) - Ordoñana, Juan R.; Carrillo, Eduvigis; Colodro-Conde, Lucía; García-Palomo, Francisco J.; González-Javier, Francisca; Madrid-Valero, Juan J.; Martínez Selva, José M.; Monteagudo, Olga; Morosoli, José J.; Pérez-Riquelme, Francisco; Sánchez-Romera, Juan F.
Abstract: The Murcia Twin Registry (MTR) is the only population-based registry in Spain. Created in 2006, the registry has been growing more than a decade to become one of the references for twin research in the Mediterranean region. The MTR database currently comprises 3545 adult participants born between 1940 and 1977. It also holds a recently launched satellite registry of university students ( N = 204). Along five waves of data collection, the registry has gathered questionnaire and anthropometric data, as well as biological samples. The MTR keeps its main research focus on health and health-related behaviors from a public health perspective. This includes lifestyle, health promotion, quality of life or environmental conditions. Future short-term development points to the expansion of the biobank and the continuation of the collection of longitudinal data.